The Best Interest of the Child in Islamic Family Law: Declarative and Enforceable Custody Protection in Indonesia and Malaysia - Viorizza Suciani Putri; Sonny Dewi Judiasih; Hazar Kusmayanti (UIN Sunan Gunung Djati Bandung, 2026)
The principle of the best interest of the child constitutes a central normative foundation for post-divorce child custody protection within Islamic family law. Although this principle is widely recognised in statutory regulations and judicial practice, its application and juridical consequences vary considerably across legal systems. This study examines the regulation and application of the best interest of the child principle in Islamic family law in Indonesia and Malaysia, with particular attention to the legal implications arising from differences in their normative and procedural designs. Employing a normative legal research method with comparative and doctrinal approaches, the study analyses legislation, the Compilation of Islamic Law, judicial decisions, and relevant scholarly literature on Islamic family law and child protection in both jurisdictions. The analytical framework draws upon the concepts of ḥaḍānah and maqāṣid al-sharīʿah to assess the relationship between custody determination and the execution of court decisions. The findings demonstrate that both Indonesia and Malaysia formally recognise the best interest of the child as the guiding principle in determining child custody under Islamic family law. However, divergent normative and procedural configurations produce distinct juridical outcomes. In Indonesia, child custody protection predominantly operates as custody protection as declarative justice, where judicial decisions establish legal entitlements without being supported by effective enforcement mechanisms. In contrast, Malaysia’s Islamic family law system reflects a model of custody protection as enforceable justice, integrating custody determinations with enforcement measures and legal sanctions for non-compliance. These findings underscore that child protection in Islamic family law is shaped not merely by normative recognition, but by the extent to which legal systems connect custody determinations with enforceable institutional mechanisms.